2018
DOI: 10.1080/03079457.2017.1416590
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Gallibacterium anatis by TaqMan fluorescent quantitative PCR

Abstract: To better understand the prevalence of Gallibacterium anatis in different poultry species, a rapid and accurate method was developed to detect G. anatis using a TaqMan fluorescent quantitative polymerase chain reaction (qPCR). Specific primers and a TaqMan probe were designed based on the reference gtxA gene sequence. The qPCR standard curve showed a good linear relationship, and the method showed good reproducibility, sensitivity, and specificity, indicating its suitability for G. anatis identification and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Real‐time fluorescence qPCR is a commonly used and reliable detection method for nucleic acids. There are 2 approaches that use qPCR: 1 based on fluorescent dyes and 1 that is targeted at specific fluorescent‐labeled DNA sequences, called probes . The invention of TaqMan probes has overcome the limitations of SYBR Green I, that is, its lack of specificity owing to its ability to bind to all DNA double‐stranded structures .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real‐time fluorescence qPCR is a commonly used and reliable detection method for nucleic acids. There are 2 approaches that use qPCR: 1 based on fluorescent dyes and 1 that is targeted at specific fluorescent‐labeled DNA sequences, called probes . The invention of TaqMan probes has overcome the limitations of SYBR Green I, that is, its lack of specificity owing to its ability to bind to all DNA double‐stranded structures .…”
Section: Discussionmentioning
confidence: 99%
“…There are 2 approaches that use qPCR: 1 based on fluorescent dyes and 1 that is targeted at specific fluorescent-labeled DNA sequences, called probes. [60][61][62] The invention of TaqMan probes has overcome the limitations of SYBR Green I, that is, its lack of specificity owing to its ability to bind to all DNA double-stranded structures. [63][64][65][66] During the extension stage of TaqMan-PCR, the DNA polymerase removes the TaqMan probe by hydrolysis, resulting in a fluorescent signal.…”
Section: Discussionmentioning
confidence: 99%
“…It has a detection rate of 97% compared with that of conventional PCR (78%) and culture (34%). Another qPCR developed by Huangfu et al (2018) that targets gtxA gene showed a better detection rate than qPCR based on gyrB gene. In general, qPCR needs lower concentration of DNA template and in addition to that it takes less time and is cost effective as compared to conventional PCR and phenotypic identification (Wang et al 2016).…”
Section: Real-time Quantitative Pcr (Qpcr)mentioning
confidence: 99%
“…The description that LOC284454 is significantly reduced in prostate, uterus, breast, and kidney cancer [44] suggests instead that LOC284454 is relatively specific and is highly expressed in HNC. [49][50][51]. Since the qPCR instrument has a multicolor fluorescent channel, the experimental group and the control group are allowed to react in the same tube with the same cDNA template, which can reduce systematic errors and improve the specificity and sensitivity of the experiment [52].…”
Section: Discussionmentioning
confidence: 99%